Injury incidence in judokas at the Spanish National University Championship - Perez-Turpin, J. A.; Penichet-Tomás, A.; Suarez-Llorca, C.; Jimenez-Olmedo, J.-M.; Jove-Tossi, M. A.; Martinez-Carbonell, J. A. (Archives of Budo, 2013)
Background and Study Aim: Understanding injury incidence rates will be a great help with regards to preventing potential future damages. It is for this reason that this study suggests studying a large number of variables. The purpose of research is the relationship of events (empirical variables) that are usually taken into account in developing injury prevention programs during the battles and training in judo tournament. Material and methods: In this research project, 57 male judokas taking part in the Spanish National University Championship in 2009 were asked to complete a retrospective questionnaire. We analysed the following events: the most commonly injured body regions, the medical diagnosis, how and when the injury happened, the type of injury, the side of the body and the type of medical attention received. For the statistical analysis, we used the SPSS statistics programme to apply the Chi-square test in order to determine the significance levels for non-parametric tests from p<.05. Results: Significant differences were found in the most commonly injured body region, the shoulder/clavicle (p<.05), and in the most common diagnosis, the sprain (p<.05). Impact injuries (p<.05) are the most common and training (p<.05) is the most dangerous time. About the type of injury, 78.38% are new injuries (p<.05) and 69.05% affect the right hand side of the body (p<.05). Doctors are the most consulted specialists, but the physiotherapists obtained the best marks. Have been out due to injury for over 21 days 36.36% of the participants, but not for the entire season. Conclusions: The most common diagnosis in university student judokas coincides with those of elite judokas, with the sprain being the most common. University student judokas have a higher rate of shoulder/clavicle injuries, while professional judokas are prone to a higher rate of knee injuries. Training is the most common moment in which injuries occur, both in university student judokas and professional judokas. New injuries are the most common types of injuries in university student judokas and, while doctors are the most consulted specialists, the physiotherapists obtained the best marks.